The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1155/2014/429359
|View full text |Cite
|
Sign up to set email alerts
|

Primary Stability of Self-Drilling and Self-Tapping Mini-Implant in Tibia of Diabetes-Induced Rabbits

Abstract: Objective. This study aimed to evaluate effects of type 1 diabetes mellitus and mini-implant placement method on the primary stability of mini-implants by comparing mechanical stability and microstructural/histological differences. Methods. After 4 weeks of diabetic induction, 48 mini-implants (24 self-tapping and 24 self-drilling implants) were placed on the tibia of 6 diabetic and 6 normal rabbits. After 4 weeks, the rabbits were sacrificed. Insertion torque, removal torque, insertion energy, and removal ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In specific cases (low bone density), the orthodontic implant is driven without decortication by a self-drilling method. An appropriate method of implant insertion is a key factor to achieve good primary stability, sufficient to the immediate loading of the orthodontic mini-implants [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In specific cases (low bone density), the orthodontic implant is driven without decortication by a self-drilling method. An appropriate method of implant insertion is a key factor to achieve good primary stability, sufficient to the immediate loading of the orthodontic mini-implants [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It may be better not to use miniscrews for patients with adverse risk factors; however, if miniscrews have to be used, longer healing periods should be allowed and specific loading protocols should be applied [81,82]. It is notable that in their animal study, Park et al [83], found that the presence of diabetes and variation in the placement system (self-drilling or self-tapping) did not affect the initial stability of orthodontic mini-implants. Generally, patients do not experience pain and discomfort following miniscrew placement [6,16,58,35].…”
Section: Patient-related Complicationsmentioning
confidence: 99%